2007
DOI: 10.7202/016148ar
|View full text |Cite
|
Sign up to set email alerts
|

Gendered dimensions of environmental health, contaminants and global change in Nunavik, Canada

Abstract: Ainsi que l’a démontré la littérature universitaire au cours des deux dernières décennies, la pollution est une importante menace potentielle à la santé à court et à long terme des êtres humains et de l’environnement naturel de l’Arctique, de même qu’elle soulève des questions de justice sociale et environnementale. Certaines études ont établi un lien entre des polluants tels que les métaux lourds, les polluants organiques de longue durée et les radionucléides, et l’usage traditionnel des nourritures locales p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Although the use of lead shotshells to hunt migratory birds was banned in Canada in 1999, they can still be legally used to harvest upland game birds and small mammals since the hunt of migratory game birds is regulated only by the federal "non-toxic" shot policy that is still in effect today (Environment Canada 2000). Despite a ban on the use of lead shot ammunition in Nunavik (Couture 2010;Couture et al 2012), a survey conducted with hunters from Inukjuak in 2004-2005 revealed that only 31 % of respondents were aware that the use of lead ammunition was banned in Nunavik communities (Kafarowski 2006). Recently, observational visits revealed that 60 % of the Nunavik stores were selling lead shotshells (Couture 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Although the use of lead shotshells to hunt migratory birds was banned in Canada in 1999, they can still be legally used to harvest upland game birds and small mammals since the hunt of migratory game birds is regulated only by the federal "non-toxic" shot policy that is still in effect today (Environment Canada 2000). Despite a ban on the use of lead shot ammunition in Nunavik (Couture 2010;Couture et al 2012), a survey conducted with hunters from Inukjuak in 2004-2005 revealed that only 31 % of respondents were aware that the use of lead ammunition was banned in Nunavik communities (Kafarowski 2006). Recently, observational visits revealed that 60 % of the Nunavik stores were selling lead shotshells (Couture 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Yet, in 2004 and 2005, in Inukjuak, a survey of hunters on the use of lead shot ammunition revealed that only 31% of respondents were aware that the use of lead ammunition was banned in the community ( 40 ). Hence, according to Serge Déry of the NRBHSS: “Since very few assessment studies have focused on this subject, we cannot be certain that the message conveyed through previous communication strategies were well received and understood.…”
Section: Discussionmentioning
confidence: 99%
“…Though the research addressing intersections of human health, climate change and gender is indeed scarce, there are some multi/transdisciplinary studies where these intersections are explored. One can mention, for example, the research carried out by Joanna Kafarowski on gendered dimensions of environmental health and contaminants in Nunavik in Canada ( 3 , 46 , 47 ). Kafarowski studies the differences between women's and men's perceptions of contaminants’ threat to human health and shows that men and women not only have different perceptions of health risks but also develop different adaptation strategies.…”
Section: Multidisciplinary Approach To Climate Change Human Health Amentioning
confidence: 99%
“…Despite the formal recognition of the importance of gender ‘lenses’ for understanding the Arctic human development ( 2 ), some researchers argue that gender perspectives in the Arctic research on climate change impacts on peoples’ health are very seldom represented ( 3 7 ). This article shows how the issues of climate and environment change, human health and gender are addressed in current research in the Arctic.…”
mentioning
confidence: 99%